2020
DOI: 10.1186/s12870-020-02359-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated warming on leaf functional traits of urban greening plants

Abstract: Background: Response and adaptation strategies of plants to the environment have always been the core issues in ecological research. So far, relatively little study exists on its functional traits responses to warming, especially in an urban environment. This information is the key to help understand plant responses and trade-off strategy to urban warming. Results: We chose the common greening trees of mature age in Beijing (Fraxinus pennsylvanica, Koelreuteria paniculata, and Sophora japonica) as the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…We found that increases in soil nutrient contents and air temperature, and decreases in air relative humidity attributable to urbanization contributed directly or indirectly to changes in plant traits closely related to the improved resource acquisition capacity of urban plants (greater leaf length, area, SLA, and leaf N and K contents) (Table 1 and Figures 2, 3) (Wright et al, 2004). This is consistent with previous studies that found urbanization favors plant species and individuals with the ability to quickly acquire resources related to higher soil fertility (Song et al, 2019) and higher air temperature (Zhu et al, 2020) in urban areas.…”
Section: Soil Nutrients and Micro-climate Influence Leaf Morphological And Nutrient Traitssupporting
confidence: 90%
“…We found that increases in soil nutrient contents and air temperature, and decreases in air relative humidity attributable to urbanization contributed directly or indirectly to changes in plant traits closely related to the improved resource acquisition capacity of urban plants (greater leaf length, area, SLA, and leaf N and K contents) (Table 1 and Figures 2, 3) (Wright et al, 2004). This is consistent with previous studies that found urbanization favors plant species and individuals with the ability to quickly acquire resources related to higher soil fertility (Song et al, 2019) and higher air temperature (Zhu et al, 2020) in urban areas.…”
Section: Soil Nutrients and Micro-climate Influence Leaf Morphological And Nutrient Traitssupporting
confidence: 90%
“…Leaf tissue thickness was positively correlated with leaf water use efficiency, and is also closely related to leaf water storage capacity [ 42 ]. Studies have shown that the increase in leaf thickness or density was beneficial to increase the distance or resistance of water diffusion from the inside of the leaf to the leaf surface, and reduce the internal water loss in the plants [ 43 ]. In this study, we found that with the increase of atmospheric particulate matter pollution, the leaf thickness showed a significant increasing trend.…”
Section: Resultsmentioning
confidence: 99%
“…2e , leaf tissue density of T3 was higher than that of T1 and T2, but there was no significant difference. Studies have shown that the increase in leaf tissue density is beneficial to reducing transpiration, thus reducing water loss of plants [ 43 ]. Meanwhile, the increase in leaf tissue density can slow down the growth of plants and store more carbon for the construction of defense organizations [ 46 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The relatively high slope for A max ‐SLA revealed a high SLA at a given unit of photosynthetic rate under warming condition. It appeared that warming may shift the plants to quick investment‐return strategy with short leaf lifespan (Zhu, Zhu, Cao, et al, 2020; Zhu, Zhu, Zhang, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Leaf photosynthesis capacity is mainly determined by the photosynthesis process per se and the arrangement of leaves within the canopy (Mantilla‐Perez & Salas Fernandez, 2017). The flag leaf's photosynthesis plays a major role as a source of grain saccharides (Sanchez‐Bragado et al, 2014; Thorne, 1973; Zhu, Zhu, Cao, et al, 2020; Zhu, Zhu, Zhang, et al, 2020). Changes in leaf morphological traits, including specific leaf area (SLA), leaf angle and leaf area, can have a major impact on photosynthesis rate, k and its distribution within the canopy (Mantilla‐Perez & Salas Fernandez, 2017; Valladares, Skillman, & Pearcy, 2002).…”
Section: Introductionmentioning
confidence: 99%